2009
DOI: 10.1111/j.1524-4733.2008.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Interchangeability of the EQ-5D and the SF-6D in Long-Lasting Low Back Pain

Abstract: Although the EQ-5D and the SF-6D are both psychometrically valid for generic outcome assessment in long-lasting low back pain, it appears that they cannot generally be used interchangeably for measurement of preference values. Sensitivity analysis examining the impact of between-measure discrepancy thus remains a necessary condition for the interpretation of the results of cost-utility evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
(66 reference statements)
4
34
0
Order By: Relevance
“…The EQ-5D score is less sensitive to change than that of the SF-6D for patients with low-back disorders. 22,24,25,32,33 These differences in health utility valuation for the same disease entity in the same cohort have prompted researchers to present the results of cost-effectiveness analyses for both valuation methods. Several studies have shown that whereas the SF-6D and ODI scores are dispersed and normally distributed, the EQ-5D scores tend to cluster and to have a bimodal distribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EQ-5D score is less sensitive to change than that of the SF-6D for patients with low-back disorders. 22,24,25,32,33 These differences in health utility valuation for the same disease entity in the same cohort have prompted researchers to present the results of cost-effectiveness analyses for both valuation methods. Several studies have shown that whereas the SF-6D and ODI scores are dispersed and normally distributed, the EQ-5D scores tend to cluster and to have a bimodal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, several studies have shown that although both the EQ-5D and SF-6D are psychometrically valid measures of health state utility in patients with low-back pain, they cannot be used interchangeably. 22,24,25,32,33 Differences in the health state utility values derived from the EQ-5D and SF-6D are substantial enough that several cost-effectiveness studies present their results using both the EQ-5D and the SF-6D as part of the sensitivity analysis. 34,35 The purpose of this study was to determine for patients with spondylolisthesis enrolled in the National Neurosurgery Quality and Outcomes Database (N 2 QOD) 2,26,27 at what threshold of increased surgical cost TLIF will become cost-prohibitive relative to PSF when both EQ-5D and SF-6D health state utility values are considered.…”
mentioning
confidence: 99%
“…3,7,10,26,35,36 This has been found to be true even in patients with low-back pain 7,24,25,27 or in patients with neck pain. 35 Theoretical causes for these differences in- clude dissimilarities in the descriptive components leading to the measurement of distinct constructs, variation in the period of recall, and the use of different valuation methods (time tradeoff for the EQ-5D and chained standard gamble for the SF-6D).…”
Section: Discussionmentioning
confidence: 93%
“…Whereas the SF-6D scores and NDI are dispersed and normally distributed, the EQ-5D tends to cluster or skew 35,36 or have a bimodal distribution. 7,27 Looking at the scatterplot between the NDI and the EQ-5D scores, a floor effect is evident as well as gaps in the EQ-5D values (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation